Benzimidazole Based Hole‐Transporting Materials for High‐performance Inverted Perovskite Solar Cells. (6th June 2022) - Tingare, Yogesh S.; Su, Chaochin; Lin, Ja‐Hon; Hsieh, Yi‐Chun; Lin, Hong‐Jia; Hsu, Ya‐Chun; Li, Meng‐Che; Chen, Guan‐Lin; Tseng, Kai‐Wei; Yang, Yi‐Hsuan; Wang, Leeyih; Tsai, Hsinhan; et al.
Abstract: Interfaces play a decisive role in perovskite solar cells' power conversion efficiency and their long‐term durability. Small‐molecule hole‐transporting materials (HTMs) have grabbed enormous attention due to their structural flexibility, material properties, and stabilities, allowing for improved operational durability in perovskite photovoltaics. This study synthesizes and investigates a new class of benzimidazole‐based small molecules,  named YJS001  and YJS003, serving as the HTMs to enable high‐efficiency mixed‐cation mixed‐halide perovskite solar cells. The benzimidazole‐based materials are dopant‐free HTMs composed of donor and acceptor building blocks that are designed to engineer the energy level alignment near the HTM/perovskite interface. Mixed‐cation mixed‐halide perovskites can be grown uniformly on both HTMs with large crystalline grains. It is discovered that the donor‐rich YJS003 ‐based solar cell exhibits a high open‐circuit voltage of 1.09 V with a champion power conversion efficiency of over 20%. Power‐dependent current–voltage characteristics of the solar cells are analyzed, from which the high performance of YJS003's excellent hole mobility and well‐aligned energy level is attributed. This work introduces a new class of benzimidazole‐based small molecules as HTMs, that paves the path for dopant free interface material development for commercialization of perovskite solar cells. Abstract : Two new hole‐transporting materials (HTMs) with acceptor‐rich (YJS001 ) and donor‐rich (YJS003 ) are synthesized and characterized for hybrid perovskite photovoltaics applications. Under similar conditions, the efficiency of HTM YJS001 and YJS003 ‐based devices is 17.43% and 20.81%, respectively. The superior performance of YJS003 over YJS001 is attributed to higher open‐circuit voltage and fill factor from good hole transport, lower trap density, and lower electric resistance of cells.